Teacher unionism reborn - Lois Weiner (Universidade Federal de Santa Maria, 2013)
This paper discusses how teachers unions have been singled out for attack because throughout the world they are the most significant barriers to this project of education reform that has been implemented in the last four decades. Teachers unions globally have experienced an astoundingly well-orchestrated, well-financed attack, and resistance elsewhere in the world has been forceful and persistent. This article presents the policies of the major teacher unions in the USA - NEA and AFT - demonstrating the efforts of an emergent resistance of activists who have questioned political actions of both national unions in the teachers battles. At last, the author defends that emergent group of activists must occupy unions in order to change their way of fighting in defense of teachers and public education.